1998
DOI: 10.1029/98gb02313
|View full text |Cite
|
Sign up to set email alerts
|

Winter fluxes of CO2 and CH4 from subalpine soils in Rocky Mountain National Park, Colorado

Abstract: Abstract. Fluxes of CO2 and CH 4 through a seasonal snowpack were measured in and adjacent to a subalpine wetland in Rocky Mountain National Park, Colorado. Gas diffusion through the snow was controlled by gas production or consumption in the soil and by physical snowpack properties. The snowpack insulated soils from cold midwinter air temperatures allowing microbial activity to continue through the winter. All soil types studied were net sources of CO2 to the atmosphere through the winter, whereas saturated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
156
6
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(183 citation statements)
references
References 32 publications
(46 reference statements)
18
156
6
3
Order By: Relevance
“…A statistically significant correlation was also found between the CO 2 and NO x fluxes (Spearman r = 0.325, p \ 0.01), and NO x and N 2 O (Spearman r = 0.342, p \ 0.01), corroborating the hypothesis that the same environmental parameters are controlling the emission of the three gases. An ongoing question with respect to trace gas flux through snow is what processes determine the observed flux increases during snowmelt runoff that other investigators have reported during this period (Brooks et al 1997;Mast et al 1998;Monson et al 2006a, b;Sommerfeld et al 1996). In fact, increases in soil moisture and nitrate concentration during spring snowmelt have been associated with increases in the amount of N 2 O measured (Brooks et al 1997;Maggiotto and Wagner-Riddle 2001;Maljanen et al 2007).…”
Section: Comparison With Other Ecosystemsmentioning
confidence: 94%
“…A statistically significant correlation was also found between the CO 2 and NO x fluxes (Spearman r = 0.325, p \ 0.01), and NO x and N 2 O (Spearman r = 0.342, p \ 0.01), corroborating the hypothesis that the same environmental parameters are controlling the emission of the three gases. An ongoing question with respect to trace gas flux through snow is what processes determine the observed flux increases during snowmelt runoff that other investigators have reported during this period (Brooks et al 1997;Mast et al 1998;Monson et al 2006a, b;Sommerfeld et al 1996). In fact, increases in soil moisture and nitrate concentration during spring snowmelt have been associated with increases in the amount of N 2 O measured (Brooks et al 1997;Maggiotto and Wagner-Riddle 2001;Maljanen et al 2007).…”
Section: Comparison With Other Ecosystemsmentioning
confidence: 94%
“…The kinetic Q 10 formulation is based on the Arrhenius equation for chemical reaction rates: the higher the temperature, the greater the number of molecules that have energies greater than the minimum activation energy and the faster the rate of microbial decay. Q 10 varies between 1.5 and 3.0 based on incubation studies or analysis of eddy covariance flux data (Oechel et al, 1997;Mast et al, 1998;Hobbie et al, 2000;Mikan et al, 2002). In contrast, Q 10f varies between 164 and 237 based on incubation of frozen soil samples (Mikan et al, 2002).…”
Section: K Schaefer and E Jafarov: A Parameterization Of Respiratiomentioning
confidence: 99%
“…which is a relationship that was empirically developed from a snowpack in similar regions as our study site (Mast et al 1998;Hubbard et al 2005). Some researchers dealt with tortuosity by either ignoring it or by letting it be equal to 1 (e.g.…”
Section: Diffusion Model (Dm) Measurement Techniquementioning
confidence: 99%
“…These findings suggest that microbial processes in underlying soil similarly may drive the flux of other gases such as nitric oxide (NO), nitrous oxide (N 2 O), and methane (CH 4 ). Therefore, these processes warrant consideration in the annual ecosystem carbon (C) and nitrogen (N) budgets of seasonally snow-covered ecosystems (Sommerfeld et al 1993;Brooks et al 1996;VanBochove et al 1996;Mast et al 1998;Yashiro et al 2006).…”
Section: Introductionmentioning
confidence: 99%